Steinfeld und Selau. Die Beziehungen zwischen dem Mutterkloster in der Eifel und dem Tochterkloster in Böhmen - Joester, Ingrid (Analecta Praemonstratensia, 2001)
The Premonstratensian Order was brought to Bohemia and Moravia by bishop Henry Zdík of Olomouc (1126-1150). He founded the Strahov monastery in Prague about 1142, to which end he asked an abbot and convent from the Steinfeld monastery in the Eifel. He then long supported the introduction of Norbertines in the Zeliv monastery near the Bohemian-Moravian border, a monastery that was originally founded for Benedictine monks. Bishop Daniel of Prague (1148-1167) had applied to Steinfeld for a monastery in the year 1148. The 33-year-old canon Gottschalk from Cologne, whose long-lived chaplain Gerlach, the future abbot of Milevsko, left an eloquent memorial for him in the so-called Continuatio Gerlaci, was destined to be the abbot. In 1149 he was sent to Zeliv together with a convent. Very soon a women’s convent followed from Dünnwald, a daughter convent of Steinfeld. Among the letters of Ulrich, provost of Steinfeld, from the years ca. 1152 - ca. 1159 one can also find letters to the abbots of Zeliv  and Strahov. Next to the women’s convent Lounovice, abbot Gottschalk founded as a daughter monastery the monastery of Geras in Lower Austria and the nearby women’s convent Pernegg, as well as the women’s convent Kounice in Moravia shortly before his death († 1184). In the archives of Steinfeld there are communications about abbatial elections in Zeliv. Zeliv remained a daughter monastery of Steinfeld until it perished in 1567. At the revival of Zeliv in the year 1643 it came under the Strahov monastery.
Keywords: steinfeld; želiv